Towards a three-dimensional hardening of schools to promote effective school safety practices in the United States: A systematic review - HaeDong Kim,; Carlson, John; Sydney Nelson, (Advances in Social Sciences Research Journal, 2021)
This article introduces a three-dimensional conceptual framework around approaches to promoting school safety practices in the United States. Our framework suggests school safety is maximized when three hardening dimensions are equally deployed – physical hardening (school’s environmental elements), procedural hardening (school’s policies and procedures), and psychological hardening (school’s strategies used to improve psychological wellbeing). A systematic review of the literature was completed and organized in the context of our three-dimensional framework to identify current hardening practices that have been empirically investigated. Among the 41 studies identified by our search criteria, 28 included physical hardening practices, 12 included procedural hardening practices, and 21 included psychological hardening practices. Few studies (n=8) included all three hardening practices within their efforts to promote school safety. The most commonly studied variables were school resource officers, locker checks, and clear and fair rules. Implications of this three-dimensional conceptual framework for future school safety research and policy directions in the United States are highlighted.